Optimal operation of microgrids considering stabilized expansion of grid-forming energy storage - MA Lihong; LIANG Yafeng; CHENG Xi; YANG Guanbao; QIU Jianhong; SHANG Lei (电力工程技术)
Grid-forming energy storage can not only have the conventional energy storage function, but also be able to improve the system inertia to meet the demand for rapid frequency and voltage regulation of microgrid with high renewable penetration. Therefore, the grid-forming energy storage technology is an important form to promote the development of microgrid technology. In this paper, to investigate the impact of energy storage control strategy, an optimal operation model of microgrids considering stabilized expansion of grid-forming energy storage is proposed. Firstly, a microgrid cluster architecture with two sub-microgrids is built. The efficiency model of each component of the microgrid cluster is determined, and different energy storage control strategies are analyzed. Based on the different energy storage control strategies, different start-up modes of diesel generators constraints are set. Secondly, with the operating cost of microgrids as the optimization objective and the diesel generator start-up mode constraints, the optimized operation model of microgrids considering stabilized expansion of grid-forming energy storage is constructed, and it is solved by the CPLEX solver. Finally, different photovoltaic penetration scenarios are set up for arithmetic. The simulation is conducted to verify that the grid-forming energy storage can effectively improve the microgrids operation economy and environmental protection. Meanwhile, appropriately increasing the microgrid cluster contact line power limit can improve the system operation economy.